A Comparative Analysis of the Effect of the Integrated Library System on Staffing Models in Academic Libraries. - Ping Fu; Fitzgerald, Moira (Information Technology & Libraries, 2013)
This analysis compares how the traditional integrated library system (ILS) and the next-generation ILS may impact system and technical services staffing models at academic libraries. The method used in this analysis is to select two categories of ILSs-two well-established traditional ILSs and three leading next-generation ILSs-and compare them by focusing on two aspects: (1) software architecture and (2) workflows and functionality. The results of the analysis suggest that the next-generation ILS could have substantial implications for library systems and technical staffing models in particular, suggesting that library staffing models could be redesigned and key librarian and staff positions redefined to meet the opportunities and challenges brought on by the next-generation ILS.